2003
DOI: 10.1097/01.ju.0000055608.92069.3a
|View full text |Cite
|
Sign up to set email alerts
|

Hounsfield Units on Computerized Tomography Predict Stone-Free Rates After Extracorporeal Shock Wave Lithotripsy

Abstract: These findings suggest that HU measurement of urinary calculi on pretreatment non-contrast computerized tomography may predict the stone-free rate. This information may be beneficial for selecting the preferred treatment option for patients with urinary calculi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
2
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(116 citation statements)
references
References 12 publications
6
102
2
6
Order By: Relevance
“…This result differs from several published studies [9][10][11]13,14]. The likely explanation for this discrepancy is that the fragility data in the present study were normalized to stone size, a procedure that was not done in any of the previous studies.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…This result differs from several published studies [9][10][11]13,14]. The likely explanation for this discrepancy is that the fragility data in the present study were normalized to stone size, a procedure that was not done in any of the previous studies.…”
Section: Discussioncontrasting
confidence: 98%
“…Helical computed tomography (CT) has been proposed as a means to predict the success or failure of lithotripsy [6,8], and a number of studies have attempted to utilize CT numbers (in Hounsfield units, which are related to x-ray attenuation values) as a predictor of stone fragility [9][10][11][12][13][14]. However, given the resolution of clinical CT and the effects of volume averaging, the simple measure of Hounsfield units in stones is most likely to correlate with stone size [15,16], and stone size correlates with the number of SW's required for comminution [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro and in vivo studies have shown that this approach can discriminate UA from non-UA stones (7)(8)(9)(10)(11). Combining the analysis of CT numbers with visual assessment of stone morphology using a wide window setting (eg, bone window) substantially improves the accuracy of stone characterization (12).…”
Section: Introductionmentioning
confidence: 99%
“…One month later, patients were reevaluated with KUB or CT. CT was performed when non-opaque stones were present or when evaluation of the stone status was insufficient with KUB. Residual fragments smaller than 3 mm were defined as clinically insignificant residual fragments (CIRF) (8). Larger stones were defined as residual stones.…”
Section: Miniperc Techniquementioning
confidence: 99%